Revisiting Goal-Setting Theory in the Contemporary Era: A Systematic Literature Review of Conceptual Evolution and Empirical Applications (2022-2025) - Emy Aurelia Ginting; Sambas Ade Kesuma (IKRAITH-EKONOMIKA, 2025)
This study aims to systematically review the conceptual development and empirical application of Goal-Setting Theory (GST) in the context of business, management, and accounting during the period 2022-2025. Using a Systematic Literature Review (SLR) approach following the PRISMA protocol, this study analyzed 56 Scopus-indexed journal articles that met the criteria. The analysis shows that publications related to GST have been quite significant over the past four years, dominated by Western European and English-speaking countries. GST is no longer limited to the context of individual motivation but has evolved into a framework used to explain innovation, sustainability, and organizational digital systems. Most studies are empirical with a quantitative approach, using GST alongside other theories such as Self-Determination Theory and Social Cognitive Theory. Overall, this study confirms that GST remains relevant to the complexity of modern organizations and provides directions for future research regarding the integration of goal setting, adaptive behavior, and AI-based technologies. Key Words: Goal-Setting Theory; motivation; organizational performance; systematic literature; management theory; digitalization; sustainability; PRIMA